Factors Affecting Human Papillomavirus Infection in Women of Reproductive Age - Mamatmusaeva, Fotima Sh. (American Journal of Bioscience and Clinical Integrity, 2025)
General Background: Human papillomavirus (HPV) is a prevalent sexually transmitted infection and a major cause of cervical cancer, affecting millions worldwide. Developing countries bear the highest burden, with HPV-linked cancers significantly impacting women’s health. Specific Background: HPV infection often remains asymptomatic but can lead to severe oncogenic transformations. Despite extensive research on HPV epidemiology, gaps remain in identifying high-risk groups and establishing effective early diagnostic methods. Knowledge Gap: While existing studies highlight HPV prevalence, limited research focuses on demographic variations and risk factors among women in Uzbekistan. Aims: This study aims to determine early diagnostic methods for HPV and assess its prevalence among women of reproductive age, considering associated oncogenic risks. Results: The study analyzed 133 women presenting with specific gynecological symptoms. Findings revealed that women aged 36–55 were 3.8 and 9.4 times more likely to have HPV than younger (19–35) and older (>56) women, respectively. Additionally, HPV prevalence was significantly higher among married women, comprising 90.2% of cases. Novelty: This research provides new insights into age and marital status as key risk factors for HPV infection, emphasizing the need for targeted diagnostic and preventive strategies. Implications: The findings underscore the necessity of implementing comprehensive HPV screening programs, particularly for high-risk age groups, to mitigate oncogenic risks and enhance women’s health outcomes.